2019
DOI: 10.1159/000495505
|View full text |Cite
|
Sign up to set email alerts
|

Fetoscopic Release of Amniotic Bands Causing Limb Constriction: Case Series and Review of the Literature

Abstract: The aim of this study was to review the perioperative complication rates and neonatal outcomes after fetoscopic release of amniotic bands that caused bilateral limb constrictions. We present 5 cases of limb constriction by amniotic bands occurring spontaneously or following fetoscopic surgery and also include a review of 21 previously published cases. The cases were analyzed for indication, surgical technique, and postoperative follow-up. In our population and the literature, the majority of the children acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 30 publications
2
34
0
1
Order By: Relevance
“…This theory therefore provides no rationale for fetoscopic treatment. Few cases in the literature 4,5,7,15‐18 like in 2 of our cases (Patients 1 and 2) described an improvement in the affected limb function after fetoscopic treatment. This would tend to support the extrinsic theory or suggest that even if bands and malformations do have a common cause, bands nonetheless have a deleterious effect on malformations.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This theory therefore provides no rationale for fetoscopic treatment. Few cases in the literature 4,5,7,15‐18 like in 2 of our cases (Patients 1 and 2) described an improvement in the affected limb function after fetoscopic treatment. This would tend to support the extrinsic theory or suggest that even if bands and malformations do have a common cause, bands nonetheless have a deleterious effect on malformations.…”
Section: Discussionsupporting
confidence: 50%
“…At last, it is debatable to perform surgery during the third trimester since expectant management or postnatal surgery should be considered as an alternative. Still, 3 surgeries during the third trimester have been reported, including one failure 9 and 2 successful cases 5 …”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Some authors reported that fetoscopic release of the amniotic bands in the case of amniotic band syndrome is feasible in order to prevent amputation and dysfunction of the extremities. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up, ultrasound scans and intervention are individually tailored and depend on the severity of ABS complications (15).…”
Section: Discussionmentioning
confidence: 99%